2021
DOI: 10.1007/s40534-021-00235-0
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into high-speed train interior noise with operational transfer path analysis method

Abstract: Passengers' demands for riding comfort have been getting higher and higher as the high-speed railway develops. Scientific methods to analyze the interior noise of the high-speed train are needed and the operational transfer path analysis (OTPA) method provides a theoretical basis and guidance for the noise control of the train and overcomes the shortcomings of the traditional method, which has high test efficiency and can be carried out during the working state of the targeted machine. The OTPA model is establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…It delivers the performance assessment of underground tunnels with other scenarios. The PL is a vital constituent in the design and analysis of the budget link of telecommunication systems [77,78]. The PL is decided from different models, and a few of them are given as follows [79,80]…”
Section: Path Lossesmentioning
confidence: 99%
“…It delivers the performance assessment of underground tunnels with other scenarios. The PL is a vital constituent in the design and analysis of the budget link of telecommunication systems [77,78]. The PL is decided from different models, and a few of them are given as follows [79,80]…”
Section: Path Lossesmentioning
confidence: 99%
“…Penelitian ini menggunakan metode kuantitatif berdasarkan pendekatan analisis jalur (path analysis). Model analisis jalur merupakan pengembangan dari metode regresi linear berganda yang memungkingkan menganalisis hubungan sebab akibat yang lebih kompleks (Burchi et al, 2020;Cheng et al, 2019;Du et al, 2021;Fu et al, 2019;M. Li et al, 2021;Qin et al, 2020;Song et al, 2021;Vaitkus et al, 2019;Xia et al, 2021).…”
Section: Metodeunclassified
“…They reported that for typical heat insulating material, the thermal conductivity should be less than 0.29 W/mK, compression strength should be higher than 0.3 MPa and nominal density should be higher than 1000 kg/m3. In order to produce symmetrical sound, the contribution of floor, roof, left and right side walls have been investigated by Li et al [48]. They observed that the generation of sound is more from floor at low speed, while it is more from roof at higher speed (greater than 300 km/h).…”
Section: Figure 1 Typical Bodyshell Of High-speed Railwaymentioning
confidence: 99%